Multidrug-Resistant Enteric Bacteria in the Water Sources of Kalgo Metropolis, Nigeria - Maidamma, Abubakar; Liman, Usman Umar; Munkaila, Tirmizhi; Gulumbe, Bashar Haruna; Abubakar, Junaidu; Aminu, Uzairu (BioScientific Review, 2023)
People in rural and impoverished regions are more likely to contract water-related illnesses such as cholera, typhoid fever, bacillary dysentery, and diarrhea because they drink polluted water at home. The main drinking water sources in Kalgo City, Nigeria, were tested for the presence of enteric bacteria. Three water samples were taken from three different locations inside the municipality using sterile procedures in triplicate. After a series of dilutions, the specimens were placed on nutrient agar, and the total number of viable bacteria was determined. Isolation and identification of the intestinal bacteria were carried out using conventional methods. Using the Kirby Bauer disk diffusion technique, the isolates were tested for antibiotic susceptibility. We used millimeters (mm) to measure the inhibitory zones. The water samples yielded the isolation of seven(7) distinct bacterial species. Shigella, Serratia, Klebsiella, Escherichia coli, Proteus, Yersinia, and Salmonella were among the pathogens that were isolated. The two most common types of these bacterial isolates were E. coli (29.63%) and Salmonella spp. (24.93%). Serratia spp. had the lowest frequency at 3.9%. Bacteria including E. coli, Salmonella, Klebsiella, Shigella, and Serratia were shown to be resistant to ampicillin, according to the sensitivity profile. On the other hand, Yersinia spp. demonstrated a moderate degree of susceptibility, whereas Proteus spp. showed a high level. Evidence of multidrug-resistant enteric bacteria in water samples emphasizes the need to evaluate and purify water before using it to enhance its quality.